Qur'anic Recitation (Murottal) And Wet Cupping Therapy For Managing Blood Pressure In Hypertension - Sari, Dwi Nopita; Mardiyono, Mardiyono; Pujiastuti, Rr. Sri Endang (Universitas Tribhuwana Tunggadewi, 2025)
Hypertension is a medical condition experienced by a person which is described by an increase in blood pressure above normal values which can cause an increase in morbidity and mortality. Complementary medicine is considered more efficacious, one of which is Al-Qur'an murotal therapy and wet cupping therapy. This study aims to find out the effect of qur’anic recitation and wet cupping therapy on blood pressure in hypertensive patients. This study used a true experimental design with a pre-test and post-test randomized control group approach, involving two groups. The intervention group was given murotal therapy for 15 minutes and cupping for 30 minutes. The control group was only given cupping therapy. The sampling technique used was simple random sampling, and the data were analyzed using repeated measures ANOVA. The results of the between-group analysis in the intervention group showed a significant reduction in both systolic (p = 0.000) and diastolic (p = 0.000) blood pressure. These findings indicate that the combination of murottal Al-Qur'an therapy and wet cupping therapy is effective in lowering blood pressure in patients with hypertension.